ANALISIS PENERAPAN MODEL PEMBELAJARAN ACTIVE LEARNING UNTUK MENINGKATKAN SELF CONFIDENCE SISWA KELAS VII PADA MATA PELAJARAN AKIDAH AKHLAK DI MTSN 03 LOMBOK TIMUR - Pathiati, Pathiati; Khaeruddin, Khaeruddin; Janniatin, Janniatin (STKIP Pesisir Selatan, 2025)
This study aims to analyze the implementation of the Active Learning model in improving the self-confidence of 7th-grade students in the Aqidah Akhlak subject at MTsN 3 East Lombok. The research employs a Classroom Action Research (CAR) method using the spiral model developed by Kemmis and McTaggart, which consists of four stages in each cycle: planning, action, observation, and reflection. The study was conducted in two cycles, each designed to observe the development of students’ self-confidence after the application of Active Learning strategies. Data collection techniques included observation and documentation. The results of the study indicate that the implementation of the Active Learning model significantly enhanced students’ self-confidence. This improvement was reflected in the students’ increased active participation, courage to speak in front of the class, and ability to express their opinions during the learning process. The improvement became more evident in the second cycle after adjustments were made based on the reflections from the first cycle.